2006
DOI: 10.1038/sj.onc.1210149
|View full text |Cite
|
Sign up to set email alerts
|

6-Mercaptopurine, an activator of Nur77, enhances transcriptional activity of HIF-1α resulting in new vessel formation

Abstract: Hypoxia-inducible factor-1a (HIF-1a) plays a central role in oxygen homeostasis. Previously, we reported that the orphan nuclear receptor Nur77 functions in stabilizing HIF-1a. Here, we demonstrate that 6-mercaptopurine (6-MP), an activator of the NR4A family members, enhances transcriptional activity of HIF-1. 6-MP enhanced the protein-level of HIF-1a as well as vascular endothelial growth factor (VEGF) in a dose-and timedependent manner. The induction of HIF-1a was abolished by the transfection of either a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 58 publications
2
50
0
Order By: Relevance
“…5,7 Likewise, effects of 6-MP on endothelial cells are described, including effects of 6-MP on purine synthesis, 20 but also enhancement of HIF1␣ activity and angiogenesis partly mediated through activation of Nur77 by 6-MP. 21 It will be extremely relevant to study 6-MP in these other vascular cells with respect to atherosclerosis and under inflammatory conditions to gain even further insight into effects of 6-MP on atherosclerosis. We have previously demonstrated that Nur77 is crucially involved in the inhibition of proliferation of venous SMCs by 6-MP.…”
Section: Pols Et Al 6-mercaptopurine In Atherosclerosismentioning
confidence: 99%
“…5,7 Likewise, effects of 6-MP on endothelial cells are described, including effects of 6-MP on purine synthesis, 20 but also enhancement of HIF1␣ activity and angiogenesis partly mediated through activation of Nur77 by 6-MP. 21 It will be extremely relevant to study 6-MP in these other vascular cells with respect to atherosclerosis and under inflammatory conditions to gain even further insight into effects of 6-MP on atherosclerosis. We have previously demonstrated that Nur77 is crucially involved in the inhibition of proliferation of venous SMCs by 6-MP.…”
Section: Pols Et Al 6-mercaptopurine In Atherosclerosismentioning
confidence: 99%
“…The HRE-tk-Luc, VEGF promoter (Ϫ2068 to ϩ50)-Luc, and Gal4-tk-Luc reporter constructs have been described previously. 8,27,29 The eukaryotic expression vectors such as pEGFP-C3-HIF-1␣ (GFP-HIF-1␣), p3XFLAG TM 7.1-FLAG-HIF-1␣, VP16-HIF-1␣, and glutathione S-transferase (GST)-fused HIF-1␣ (pEBG-HIF-1␣) and truncated constructs were described previously. 27,29 The Gal4 DBD-fused ROR␣1, FLAG-tagged full-length and truncated ROR␣1 constructs, HA-tagged ROR␣4, and antisense (AS)-ROR␣1 plasmids were constructed by conventional rDNA technology.…”
Section: Plasmids and Transient Transfectionmentioning
confidence: 99%
“…27,29 Immunoprecipitation and subcellular fractionation was carried out basically as described previously. 27,28 …”
Section: Western Blotting Immunoprecipitation and Subcellular Fractmentioning
confidence: 99%
See 1 more Smart Citation
“…Azathioprine (Aza) caught our attention because of its described beneficial effects on endothelial cells (ECs). Aza increases EC survival, 17 in contrast to sirolimus, which induces apoptosis, causing the thrombotic problems in sirolimus-coated coronary stents, 18 or cyclosporine A that is toxic to ECs and provokes vasculopathy. 19 We and others have previously shown that Aza maintains the contractile phenotype of smooth muscle cells 20,21 and has an anti-inflammatory effect in macrophages 22 and T cells.…”
mentioning
confidence: 99%